Perioperative outcomes of esophagectomy preceded by the laparoscopic transhiatal approach for esophageal cancer. Issue 5 (1st July 2014) - Shiozaki, A.; Fujiwara, H.; Murayama, Y.; Komatsu, S.; Kuriu, Y.; Ikoma, H.; Nakanishi, M.; Ichikawa, D.; Okamoto, K.; Ochiai, T.; Kokuba, Y.; Otsuji, E.
Summary: This study was designed to determine the efficacy of esophagectomy preceded by the laparoscopic transhiatal approach (LTHA ) with regard to the perioperative outcomes of esophageal cancer. The esophageal hiatus was opened by hand-assisted laparoscopic surgery, and carbon dioxide was introduced into the mediastinum. Dissection of the distal esophagus was performed up to the level of the tracheal bifurcation. En bloc dissection of the posterior mediastinal lymph nodes was performed using LTHA . Next, cervical lymphadenectomy, reconstruction via a retrosternal route with a gastric tube and anastomosis from a cervical approach were performed. Finally, a small thoracotomy (around 10 cm in size) was made to extract the thoracic esophagus and allow upper mediastinal lymphadenectomy to be performed. The treatment outcomes of 27 esophageal cancer patients who underwent LTHA -preceding esophagectomy were compared with those of 33 patients who underwent the transthoracic approach preceding esophagectomy without LTHA (thoracotomy; around 20 cm in size). The intrathoracic operative time and operative bleeding were significantly decreased by LTHA . The total operative time did not differ between the two groups, suggesting that the abdominal procedure was longer in the LTHA group. The number of resected lymph nodes did not differ between the two groups. Postoperative respiratory complications occurred in 18.5% of patients treated with LTHA and 30.3% of those treated without it. The increase in the number of peripheral white blood cells and the duration of thoracic drainage were significantly decreased by this method. Our surgical procedure provides a good surgical view of the posterior mediastinum, markedly shortens the intrathoracic operative time, and decreases the operative bleeding without increasing major postoperative complications.